Komparativna analiza učnih načrtov za likovno vzgojo - Herzog, Jerneja (Revija za elementarno izobraževanje, 2009)
Comparing teaching plans is always difficult. The article presents an analysis of Art Education teaching plans in Slovenia, Finland, Germany and England. The analysis only includes the lower grades, from the first to fourth years of primary school. We decided to limit our research to this range because all the mentioned countries have very different programs and systems, but the age level of pupils up to the fourth grade is the same everywhere. Ananalysis of teaching plans shows that the Slovenian and German teaching plans for art education have the most points in common. The analysis also showed that the Finnish and English teaching plans for art education are very open while the Slovene and German plans are very closed. The one point that all the teaching plans have in common is artistic education with artistic activities through which pupils get to know their surrounding environment, sensitive observation, experience and imagination.
Keywords: vzgoja in izobraževanje; likovna vzgoja; učni načrti; kurikulum; curriculum; razredni pouk; komparativna analiza